SOSIALISASI PELUANG KARIER AKUNTANSI PADA ERA MILENIAL DI SMK ISLAM AL HIKMAH MAYONG JEPARA - Puji Setya Sunarka; M. Rifki Bakhtiar (Universitas YPPI Rembang, 2024)
The community service activity is motivated by the development of technology that affects science, especially in the field of accounting. This technological development indirectly affects the economy and business sector, where human work is now starting to be replaced by machines. The accounting profession is still very much needed because of its function in decision making and control. On the other hand, from the data obtained in 2022, SMK graduates ranked first in contributing to unemployment. The purpose of this community service is to increase knowledge, understanding, and offerings to prepare accounting majors in the millennial era to face digitalization. Interaction will be created through the provision of material and question and answer sessions. The results obtained through this activity will broaden students’ knowledge and insight into current digital developments and contribute to increasing their awareness of how to prepare higher education that is acceptable in the job market.Keywords: socialization; career; accounting field